Utilizing Online Gambling: Mengkaji Faktor Fenomena Judi Online Scatter di Desa Pahieme - Erino Nainggolan; Muhammad Iqbal (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2024)
The phenomenon of online scatter gambling games has become a habit that people use for entertainment. Online gambling can be used by people anywhere. Many groups of people are involved in online gambling, including children, teenagers, adults and the elderly. The community created an association in the form of a lapo as a place to make it easier to interact and build relationships while playing online gambling. This research aims to reveal the background of the community involved in playing online scatter gambling in Pahieme village as well as the interaction process used by the community when playing online gambling. Data collection used in this research was observation, direct interviews, and documentation. The results of this research show that people are involved in playing online gambling because they are involved with friends, to satisfy themselves and to make a profit. The relationships that arise are used by people during the playing process to facilitate interaction and buying and selling chips or coins, so that there is a very long online gambling activity every day. So the negative impacts include addiction, loss of money and stress, while the positive impacts include entertainment, fun and increasing income.